(untitled) (Baltic Journal of Sport and Health Sciences, 2022)
Background. The measures of social and physical isolation during the period of the Covid-19 pandemic had an influence on people’s way of life and mental health. It was noticed one of the biggest problems during the period of the Covid-19 pandemic was an increase of negative emotions and decrease of physical activity among people that usually do sports. In the article, the main attention is paid to emotional states of people attending sports and health clubs during and after the period of the Covid-19 pandemic. Methods. The following research methods were applied: SAN questionnaire, interview survey and the situation anxiety assessment scale by Spielberger and Khanin. A Chi square (χ²) test was applied for the comparison of the results between the researched groups. The research was performed in the academic year 2021/2022 and 97 physically active people that did sports in sports and health clubs, including 35 women and 62 men, were researched. Results. The results revealed the people attending sports and health clubs assessed their well-being during the period of the Covid-19 pandemic in the following way: even 46 percent of the researched assessed it as low, 37 percent indicated the average level and 17 percent – the high level. However, after the Covid-19 pandemic, just 24 percent of the researched assessed their well-being as low, 34 percent indicated the average level and 42 percent – the high level. The people that attended sports and health clubs assessed their activity during the pandemic: 48 percent indicated the low level, 31 percent – the average level, and 21 percent – the high level. These indexes became better after the pandemic: 28 percent assessed their activity as low and average, and 44 percent – as high. The pandemic restrictions also had a big influence on the mood of those researched: the level of the mood of the researched attending sports and health clubs was low with even 47 percent, average with 23 percent, and high with 30 percent. However, the mood indexes were distributed after the pandemic: 22 percent indicated the low level, 25 percent – the average level and 53 percent – the high level. It was noticed even 58 percent of the researched assessed their situation anxiety as high during the pandemic, 23 percent – as average, and 19 percent – as low. Meanwhile, after the pandemic, the same researched assessed their situation anxiety in the following way: 49 percent – as low, 25 percent – as average, and 26 percent – as high. Conclusions. The indexes of well-being, activity, mood and situation anxiety of people attending sports and health clubs were much better after the Covid-19 pandemic than during the period of the Covid-19 pandemic. Keywords: Covid-19, sports and health clubs, emotional state, well-being, activity, mood, situation anxiety